(untitled) - Doff, Adrian (Cambridge, 1995)
Listening 1 develops students' ability to understand real-life spoken English through recordings of spontaneous, natural speech, which have been carefully selected and edited for pre-intermediate learners. The activities are designed to encourage students to draw on their own natural listening strategies and to apply them effectively in the context of language learning.
Keywords: English language,English language,Tiếng Anh,Tiếng Anh; Listening,Textbooks for foreign speakers,Kỹ năng nghe,Giáo trình dành cho người nước ngoài